RETRACTED ARTICLE: Identification of a novel Na+-coupled Fe3+-citrate transport system, distinct from mammalian INDY, for uptake of citrate in mammalian cells - Jiro Ogura (Nature Portfolio, 2018)
Abstract NaCT is a Na+-coupled transporter for citrate expressed in hepatocytes and neurons. It is the mammalian ortholog of INDY (I’m Not Dead Yet), a transporter which modifies lifespan in Drosophila. Here we describe a hitherto unknown transport system for citrate in mammalian cells. When liver and mammary epithelial cells were pretreated with the iron supplement ferric ammonium citrate (FAC), uptake of citrate increased >10-fold. Iron chelators abrogated the stimulation of citrate uptake in FAC-treated cells. The iron exporter ferroportin had no role in this process. The stimulation of citrate uptake also occurred when Fe3+ was added during uptake without pretreatment. Similarly, uptake of Fe3+ was enhanced by citrate. The Fe3+-citrate uptake was coupled to Na+. This transport system was detectable in primary hepatocytes and neuronal cell lines. The functional features of this citrate transport system distinguish it from NaCT. Loss-of-function mutations in NaCT cause early-onset epilepsy and encephalopathy; the newly discovered Na+-coupled Fe3+-citrate transport system might offer a novel treatment strategy for these patients to deliver citrate into affected neurons independent of NaCT. It also has implications to iron-overload conditions where circulating free iron increases, which would stimulate cellular uptake of citrate and consequently affect multiple metabolic pathways.